2007
DOI: 10.1088/0953-4075/40/14/003
|View full text |Cite
|
Sign up to set email alerts
|

Current enhancement of a He+ion beam by optical pumping

Abstract: We observed that the current of a He+ ion beam generated from an RF ion source was enhanced by optical pumping (OP) using 1083 nm resonance radiation. The ion current enhancement became more remarkable with higher pressure and higher OP radiation density. The ion beam current with an OP irradiation of 0.5 W cm−2 at 65 Pa was 1.25 times larger than that without OP. We interpreted this OP effect on the ion current in terms of Penning ionization (PI) of He (23S) by He (23P). From the pressure dependence of the OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Since the spin-polarized He + ions are generated from spin-polarized He*, higher spin polarization of He + (PHe + ) is obtained with a higher spin polarization of He* (PHe*). 2 The relationship between PHe* and the OP radiation density has not been reported, although the nuclear polarization of 3 He as a function of the OP radiation intensity has been investigated by Nacher et al 3 In the present study, the relationship between PHe* in an active discharge and the OP radiation density is discussed from an analysis of the rate equations of OP. We found that PHe* decreased as the OP radiation density increased in the range above 0.05 W cm 2 .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Since the spin-polarized He + ions are generated from spin-polarized He*, higher spin polarization of He + (PHe + ) is obtained with a higher spin polarization of He* (PHe*). 2 The relationship between PHe* and the OP radiation density has not been reported, although the nuclear polarization of 3 He as a function of the OP radiation intensity has been investigated by Nacher et al 3 In the present study, the relationship between PHe* in an active discharge and the OP radiation density is discussed from an analysis of the rate equations of OP. We found that PHe* decreased as the OP radiation density increased in the range above 0.05 W cm 2 .…”
Section: Introductionmentioning
confidence: 72%
“…Under various intensities of the OP radiation, the sum of the He* and He 2 3 P atom populations are almost constant in the steady state of discharge. 2 It is noted that the dipole transition between 2 3 S1 and 2 3 P is close to the circumstance of a two-level system, because decay into 1 1 S0 from this system is forbidden. Figure 3 shows PHe* as a function of the OP radiation density for two cases of the He pressure in the discharge bulb ( than that of 46 Pa.…”
Section: Sample Preparationmentioning
confidence: 95%